Salt [videorecording (DVD)] - Wimmer, Kurt, 1964-; Di Bonaventura, Lorenzo; Noyce, Phillip; Perkash, Sunil, approximately 1970-; Jolie, Angelina, 1975-; Olbrychski, Daniel; Schreiber, Liev; Ejiofor, Chiwetel; Braugher, Andre (Sony Pictures Home Entertainment, 2010)
As a CIA officer, Evelyn Salt swore an oath to duty, honor and country. Her loyalty will be tested when a defector accuses her of being a Russian spy. Salt goes on the run, using all her skills and years of experience as a covert operative to elude capture. Her efforts to prove her innocence only serve to cast doubt on her motives, as the hunt to uncover the truth behind her identity continues.